2020
DOI: 10.3390/e22080839
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Oscillation on Escape Dynamics of Classical and Quantum Open Systems

Abstract: We study the effect of self-oscillation on the escape dynamics of classical and quantum open systems by employing the system-plus-environment-plus-interaction model. For a damped free particle (system) with memory kernel function expressed by Zwanzig (J. Stat. Phys. 9, 215 (1973)), which is originated from a harmonic oscillator bath (environment) of Debye type with cut-off frequency wd, ergodicity breakdown is found because the velocity autocorrelation function oscillates in cosine function for asymptotic time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It should be noted here that the concept of self-oscillations is widely used in the modern science. For example, we refer the reader to [6][7][8][9][10][11], and for low-frequency self-oscillations, to [12].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted here that the concept of self-oscillations is widely used in the modern science. For example, we refer the reader to [6][7][8][9][10][11], and for low-frequency self-oscillations, to [12].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Barik and Ray developed the scheme employing quantum Brownian motion for multiplicative noise [29]; Bao and co-workers demonstrated that the effective coefficient of diffusion of a particle driven by quantum thermal noise in a biased periodic potential is less than the classical version when the biasing force attains its critical value obtained from the QGLE [24]. The steady escape rate of a self-oscillated system from a metastable potential exhibited in molecular dynamics simulations a nonmonotonic dependence at the cut-off frequency of a harmonic oscillator bath [30], and the magnitude and direction of the average current were affected by the nonlinear quantum dissipation in a PIMC approach [31]. Here, for finite temperatures, we shall apply the QGLE and PIMC methods mentioned above to consider the effect of disorder on the transport dynamics of a particle in the quantum domain and propose an effective classical disorder potential which is important in understanding the dynamic behavior in quantum disorder potentials.…”
Section: Introductionmentioning
confidence: 99%